Automatic underground bicycle parking system - Bharadwaja, Julian; Than Lin; Manukid Parnichkun (Pathum Thani : Asian Institute of Technology, 2017)
Nowadays, at the campus, apartments, buildings, and etc., the number of bicycles used mostly by citizens are getting bigger in quantity as parking of bicycles in front of build- ings and dorm takes up so much space and also making the students to park their bicycle mostly on the sidewalks. This is one of the causes of students losing their bicycles as the bicycles parked on sidewalks are more vulnerable to be stolen. Automatic underground bicy- cle parking system could play a vital role in all such inconvenience for students, pedestrians and citizens who are using the sidewalks in the cities as this system would make the bicy- cles to park their bicycles in an arranged manner. The aims of project are for construction and designing of Arduino based AUTOMATIC UNDERGROUND BICYCLE PARKING SYSTEM by using servo motors, DC motors, LEDs, LCD, switches, pulley, Arduino Uno, Arduino Mega, and Arduino Nano.
A capstone project submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering Mechatronics Engineering, School of Engineering and Technology
Capstone Project (B.Sc.)-Asian Institute of Technology, 2017
Keywords: Bicycle parking